Effectiveness of Incentive Provision Based on Partner Performance, Achievement, and Personnel Loyalty - Annisa, Zahra (Sekolah Menengah Kejuruan (SMK) Pustek, 2022)
In improving employee performance, it is necessary to pay attention to these factors and pay attention to the needs of employees, among others by providing incentives. This study aims to determine and analyze how effective the application of incentives is related to performance, achievement and employee loyalty. The method used in this study uses a qualitative approach based on phenomenology. The results of this study are based on quantitative data calculations and nominally from the company it is categorized as appropriate, but technically there are still many discrepancies found such as excessive workload, irrational targets. This causes the performance, achievement and loyalty of employees to decrease so that it has an impact on the incentives received by employees.